Indicators assessment of social impact study in the quarrying industry: experience at Bukit Lagong, Selangor Darul Ehsan / Sa'diah Sahat ... [et al.] - Sahat, Sa'diah; Hilmi, Zulkifli Ab Ghani; Abd Rashid, Saharani; Mokhtar, Mazura; Karim, Razali (2008)
This paper arises from a consultation work conducted from August to October 2007 with the Department of Minerals and GeoScience, Malaysia regarding the social impact study of the quarrying industry in the Bukit Lagong area, Selangor Darul Ehsan. The quarrying industry plays a major role in the development of the country by providing the materials needed in the foundation and construction of infrastructure such as roads, highways, commercial and residential buildings, However, the Quarry Resource Planning for the State of Selangor, Kelantan, Terengganu, Sabah and Sarawak under the Eighth Malaysia Plan pointed out some main issues affecting the quarrying industry. One of them is the need to ensure that quarrying is carried out in a safe, environmentally friendly and sustainable manner. This is indeed true for quarries operating close to urban areas such as in the case of the Bukit Lagong area, The objective of the study is to assess the perception of communities close to quarry sites with regard to the quality of environment (dust, water and noise), road safety, blasting effect, condition of roads, personal and family health. Information was gathered through a sample survey of 334 households based on questionnaire that consists of close and open-ended questions and direct observation by the research group. Analysis on the perception was done through frequency counts (percentages) and tabulation. The highest implications from each issue gathered from the respondents are: damages to roads (potholes, uneven roads, surface of roads being stripped, etc) - 90%, driving attitudes of lorry drivers - 85.2%, high risk of road accidents (related to driving attitude, heavy traffic) - 84.8% and dust / airborne particles from moving lorries and dusty roads (paved & unpaved) - 79.4%